Phosphoenolpyruvate Carboxykinase Is Involved in the Decarboxylation of Aspartate in the Bundle Sheath of Maize - Wingler, Astrid (American Society of Plant Physiologists, 1999)
We recently showed that maize (Zea mays L.) leaves contain appreciable amounts of phosphoenolpyruvate carboxykinase (PEPCK; R.P. Walker, R.M. Acheson, L.I. Técsi, R.C. Leegood [1997] Aust J Plant Physiol 24: 459–468). In the present study, we investigated the role of PEPCK in C(4) photosynthesis in maize. PEPCK activity and protein were enriched in extracts from bundle-sheath (BS) strands compared with whole-leaf extracts. Decarboxylation of [4-(14)C]aspartate (Asp) by BS strands was dependent on the presence of 2-oxoglutarate and Mn(2+), was stimulated by ATP, was inhibited by the PEPCK-specific inhibitor 3-mercaptopicolinic acid, and was independent of illumination. The principal product of Asp metabolism was phosphoenolpyruvate, whereas pyruvate was a minor product. Decarboxylation of [4-(14)C]malate was stimulated severalfold by Asp and 3-phosphoglycerate, was only slightly reduced in the absence of Mn(2+) or in the presence of 3-mercaptopicolinic acid, and was light dependent. Our data show that decarboxylation of Asp and malate in BS cells of maize occurs via two different pathways: Whereas malate is mainly decarboxylated by NADP-malic enzyme, decarboxylation of Asp is dependent on the activity of PEPCK.